Gandhian Impression on Modi - Kumar, Sanjay; Puntasen, Apichai (Journal of Dhamma for Life, 2025)
In India’s extensive and diverse political chronicles, only a select few have wielded an enduring impact comparable to that of Mahatma Gandhi and Narendra Modi. Despite the considerable temporal and ideological distance separating their perspectives and epochs, the style and policies of PM Modi evinces a clear and indelible legacy of Gandhi. PM Modi inaugurated several policies and schemes for the development of Indian people. This paper consists of Gandhian thoughts which have been followed by PM Modi. They also include several schemes which are based on Gandhian thoughts. The notion of "Swadeshi" or self-reliance, espoused by Mahatma Gandhi, remains a pivotal facet of India’s socio-political and economic landscape under PM Modi’s stewardship. PM Modi’s government has executed policies and legislations that bolster the "Make in India" campaign and conform to Swadeshi principles, intending to foster the growth of domestically produced goods. The Ayushman Bharat initiative, which was initiated during Modi’s tenure, endeavors to furnish complimentary health insurance to the underprivileged strata of society, with a focus on financial safeguards and preventive healthcare measures. While there may be differing opinions on their legacies but Mahatma Gandhi and PM Modi both have left an indelible mark on India’s history and continue to shape the country’s future.